GREED - Corner, Creative (Journal of Pakistan Psychiatric Society, 2023)
Humans have been exploiting glaciers through unsustainable practices like overextraction, hydropower projects, reckless tourism, and mining, driven by their greed for water, power, and profit. Rising sea levels, loss of biodiversity, and water scarcity are all consequences of this avarice threatening glaciers and their ecosystems. Stricter laws, community involvement, ethical travel, and investments in renewable energy are needed to counteract this in order to preserve these natural treasures and secure a sustainable future. By recognising the perils of greed and taking proactive steps to address its role in exploitation of nature and its resources such as glaciers, we can protect these magnificent natural wonders and ensure a sustainable future for ourselves and future generations. Thus, it is imperative for us to understand that glaciers are not just frozen rivers, but they are vital components of our planet’s ecosystems, and their preservation is intricately connected to our own existence.